Understanding globin regulation in β-thalassemia: it’s as simple as α, β, γ, δ - Bank, Arthur (American Society for Clinical Investigation, 2005)
A vast excess of α-globin production and inadequate γ-globin compensation lead to the development of severe anemia in human β-thalassemia. Newly identified modifiers of α- and γ-globin synthesis and insights into the mechanisms of globin regulation provide the tools for potential new approaches to treating this and other red blood cell disorders. In the study by Han and colleagues in this issue of the JCI, the activity of a heme-regulated protein, HRI, is shown to modulate the accumulation of excess α-globin chains in murine β-thalassemia and to decrease the severity of the disease.